Exploring Consumer Perceptions Of E-Wallet Usage In Shopping Practices: A Qualitative Study In Indonesia - Hendri Mauliansyah; Kiki Putri Amelia (SUMBER INFORMASI MANAJEMEN BISNIS DAN AKUNTANSI, 2025)
This study explores consumer perceptions of e-wallet usage in shopping practices within the Indonesian context, where digital financial services are rapidly reshaping payment behavior. Using a qualitative design, data were collected through semi-structured interviews and focus groups with 30 participants representing diverse ages, income levels, and geographic locations. Thematic analysis revealed three key findings. First, convenience, transaction speed, promotional incentives, and integration with other digital services emerged as the primary benefits driving adoption, particularly among younger and tech-savvy consumers. Second, concerns over data security, fraud, hidden fees, and technical glitches remained significant barriers, limiting broader trust and acceptance. Third, demographic factors, especially age and digital literacy, strongly shaped adoption patterns, with younger generations showing higher enthusiasm compared to older users. The study also highlights the influence of social dynamics, as peer recommendations and family norms played a critical role in shaping attitudes toward e-wallets. These findings extend the literature by emphasizing the interplay between convenience, security, social influence, and demographic diversity in consumer adoption of digital payment systems in emerging markets. The research contributes theoretical and practical insights for e-wallet providers and policymakers seeking to foster inclusive digital financial ecosystems and enhance consumer trust in the rapidly expanding digital economy.